Answer:
Horizontal Asymptote → y = 17
Explanation:
Given function is f(x) =
![(2)/(5)(16)^(x+13)+17](https://img.qammunity.org/2022/formulas/mathematics/college/96ashxa4btqkj7mkpmb04j4rn1c44gdjmf.png)
Here, the parent function is g(x) =
![(2)/(5)(16)^x](https://img.qammunity.org/2022/formulas/mathematics/college/dullmnpmwdel6e5agmw6sux3jpyakzksxn.png)
Parent function has a horizontal asymptote as y = 0
If the function g(x) is shifted 13 units left and 17 units up, new function will be f(x) =
![(2)/(5)(16)^(x+13)+17](https://img.qammunity.org/2022/formulas/mathematics/college/96ashxa4btqkj7mkpmb04j4rn1c44gdjmf.png)
When the parent function is shifted 17 units up, horizontal asymptote shifts 17 units upwards.
Therefore, horizontal asymptote of the image function becomes y = 17.